Performance of MLI Seams between 293 K and 20 K. Issue 1 (March 2020) - Johnson, W L; Chato, D J
Abstract: The performance of multilayer insulation systems (MLI) are often determined not by the bulk acreage insulation but rather by the design details that allow the insulation to be attached to the hardware it is insulating. To help understand the impacts of multiple different types of seams on blanket performance, calorimeter testing was performed at Glenn Research Center. Seams investigated included interleaved seams, butt seams, and overlapped seams; the latter two types of seams with multiple sub-blanket offsets built into the seam. Results showed that the interleaved seam had the best performance, and butt seams outperformed overlapped seams. Furthermore, if overlap seams are used, the sub-blankets should be overlapped by less than two inches.